(untitled) (Research, Society and Development, 2022)
This study aimed to record the entry of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) in the state of Amapá, Brazil, and discuss the possible reasons for its non-establishment. Fruit sampling was carried out in three municipalities (Macapá, Porto Grande and Santana) and fruits from other units of the federation were purchased at marketing points in Macapá. A survey was also carried out with McPhail and Jackson traps in four municipalities (Macapá, Mazagão, Porto Grande and Santana). Specimens of C. capitata were captured in McPhail and Jackson traps in the municipalities of Macapá and Santana. Specimens were also obtained from guavas from the state of São Paulo, acquired in a commercial establishment in Macapá. We argued that the low incidence of C. capitata and its non-establishment in the region may be due to unfavorable climatic conditions for the species.